Multiphysics simulation of emerging food processing technologies - Knoerzer, Kai (Wiley, 2011)
"Multiphysics simulation of emerging food processing technologies discusses how multiphysics modeling - i.e., the simulation of the entire process comprising the actual equipment, varying process conditions and the physical properties of the food to be treated - can be applied in the development, optimization and scale-up of emerging food processing technologies and shows the most recent research outcomes to demonstrate process efficiency and the impact on scalability, safety and quality. Technologies covered include: high pressure processing, high pressure thermal sterilization, radiofrequency, microwave, ultrasound, ultraviolet, and pulsed electric fields processing. The book is targeted to food and process engineers, food technologists, equipment designers, and research and development personnel including microbiologists, both in industry and academia. Multiphysics simulation of emerging food processing technologies fully describes the importance and the methods for applying multiphysics modeling for the design, development, and application of these technologies"- Resumé vydavatel
Keywords: potravinářství; inovace; food industry and trade; innovations; elektronické knihy; sborníky; electronic books; papers of several authors